2018
DOI: 10.1037/pag0000236
|View full text |Cite
|
Sign up to set email alerts
|

When does cognitive decline begin? A systematic review of change point studies on accelerated decline in cognitive and neurological outcomes preceding mild cognitive impairment, dementia, and death.

Abstract: Older adults who ultimately develop dementia experience accelerated cognitive decline long before diagnosis. A similar acceleration in cognitive decline occurs in the years before death as well. To evaluate preclinical and terminal cognitive decline, past researchers have incorporated change points in their analyses of longitudinal data, identifying point estimates of how many years prior to diagnosis or death that decline begins to accelerate. The current systematic review aimed to summarize the published lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 103 publications
(408 reference statements)
8
103
0
1
Order By: Relevance
“…However, we expect to find more pronounced differences as more assessments were included, since a longer follow-up would be the proper way to study changes in these cognition trajectories. Nonetheless, according to the systematic review of Karr et al (2018), change points for cognitive abilities ranged from 3 to 7 years before mild cognitive impairment diagnosis. Thus the study of preclinical differences could be useful on the early detection of cognitive change [50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we expect to find more pronounced differences as more assessments were included, since a longer follow-up would be the proper way to study changes in these cognition trajectories. Nonetheless, according to the systematic review of Karr et al (2018), change points for cognitive abilities ranged from 3 to 7 years before mild cognitive impairment diagnosis. Thus the study of preclinical differences could be useful on the early detection of cognitive change [50].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, according to the systematic review of Karr et al (2018), change points for cognitive abilities ranged from 3 to 7 years before mild cognitive impairment diagnosis. Thus the study of preclinical differences could be useful on the early detection of cognitive change [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the use of the bootstrapping analysis not only allows us to capture parameter estimates and standard errors more accurately, but enables the statistical comparison of change-points among different cognitive measures, greatly extending the work of previous studies. [14] In summary, we found that the cognitive measure to show the earliest change in rates of decline in preclinical AD was visuospatial ability rather than episodic memory. Using change-point analyses with bootstrapping can reveal the temporal patterns of accelerated cognitive decline in preclinical AD and may help guide the development of tools for participant screening in clinical trials.…”
Section: Cvlt-ld Bvrtmentioning
confidence: 71%
“…Signs of cognitive decline can be evident in adults as young as their twenties [ 12 ]. Rates of cognitive deterioration have been found to accelerate in the 15 years preceding death—this includes 3 to 7 years before mild cognitive impairment diagnosis and to 1–11 years before dementia is diagnosed [ 13 ]. The causes of poor brain health are multi-factorial, quite often having the same modifiable risk factors as cardiovascular disease such as obesity, physical inactivity, smoking, diabetes mellitus and depression [ 14 ].…”
Section: Introductionmentioning
confidence: 99%